The influence of mental health, psychosocial factors and educational skills on educational aspirations among indigenous Sámi and nonindigenous adolescents in the Arctic - Bania, Elisabeth; Eckhoff, Christian; Kvernmo, Siv (Psychiatric Research Unit, Region Zealand, 2015)
Background: Mental health and psychosocial factors seem to influence the educational aspirations of adolescents, which are also known to be related to educational skills and sociodemographic factors such as gender, ethnicity, religious affiliation, and socioeconomic status. Previously, the relationship between educational aspirations and mental health, psychosocial factors, and educational and sociocultural conditions has not been investigated in Arctic adolescents. Objective: We aimed to investigate the influence of mental health, psychosocial factors, and educational skills on educational aspirations among multiethnic adolescents in an Arctic sociocultural context. Method: The Norwegian Arctic Adolescent Health Study, which was conducted from 2003 to 2005, is a cross-sectional school-based survey. Individuals from the total population of 5877 tenth graders between the ages of 15 and 16 years were invited to participate in the study. Of this group, 4881 participated (response rate, 83%), 50.1% were female, and 10% were indigenous Sámi. Results: Educational skills as measured by higher average mark were associated with higher aspirations; lower average mark was associated with lower aspirations. Weaker peer support and stronger parental involvement influenced aspirations in individuals with both higher and lower aspirations. Adolescents with lower rates of hyperactivity and inattention problems reported higher aspirations, whereas adolescents with emotional problems showed a greater inclination toward intermediate aspirations. In addition, males and Sámi adolescents showed lower aspirations and were more likely to be located in more remote and northern areas. Conclusions: This study confirmed earlier findings that educational skills have a strong influence on educational aspirations. However, mental health as well as social, familial, and residential contexts must be addressed to foster adolescents’ educational aspirations. Negative peer support for master’s and vocational degrees should be addressed by families ...